2017
DOI: 10.3748/wjg.v23.i10.1851
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous intraductal radiofrequency ablation for treatment of biliary stent occlusion: A preliminary result

Abstract: AIMTo assess the feasibility and effectiveness of a novel application of percutaneous intraductal radiofrequency (RF) for the treatment of biliary stent obstruction.METHODSWe specifically report a retrospective study presenting the results of percutaneous intraductal RF in patients with biliary stent occlusion. A total of 43 cases involving biliary stent obstruction were treated by placing an EndoHPB catheter and percutaneous intraductal RF was performed to clean stents. The stent patency was evaluated by chol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…It has been the preferred minimally invasive method to treat solid 5) reported a prospective study using a bipolar radiofrequency catheter to clear blocked SEMSs in 9 patients, with a median stent patency of 102.5 days. Subsequently, other investigators have reported techniques using PTCD or ERCP to reopen occluded SEMSs, although retrospective designs limited the statistical power of these results (6)(7)(8)(9). It has been demonstrated that the duration of SEMS patency can be prolonged by ILBT using high-dose-rate 192 Ir.…”
Section: Discussionmentioning
confidence: 99%
“…It has been the preferred minimally invasive method to treat solid 5) reported a prospective study using a bipolar radiofrequency catheter to clear blocked SEMSs in 9 patients, with a median stent patency of 102.5 days. Subsequently, other investigators have reported techniques using PTCD or ERCP to reopen occluded SEMSs, although retrospective designs limited the statistical power of these results (6)(7)(8)(9). It has been demonstrated that the duration of SEMS patency can be prolonged by ILBT using high-dose-rate 192 Ir.…”
Section: Discussionmentioning
confidence: 99%
“… 206 In patients developing stent obstruction, few short series have shown the benefit of RFA and balloon sweep in recanalization. 207 208 209 One recent randomized controlled trial from China showed that endoscopic RFA with stenting significantly increases stent patency and survival in patients with extrahepatic cholangiocarcinoma. 210 …”
Section: Methodsmentioning
confidence: 99%
“…There have been two studies examining the endoscopic approach and three studies examining the percutaneous approach of RFA for occluded SEMS (Table 4). [68][69][70][71][72] Although the primary disease and stricture site vary between studies, the patency period after RFA ranges between 102.5 and 234 days, which is equal to or better than the period of reintervention following procedures other than RFA. 73,74 Only one comparative study reported that the mean stent patency time after reintervention was significantly longer in the RFA group than the control group (119.5 vs. 65.3 days, P = 0.03).…”
Section: Rfa For Occluded Semsmentioning
confidence: 99%